Trained Immunity Confers Prolonged Protection From Listeriosis - Théroude, Charlotte; Reverte, Marta; Heinonen, Tytti; Ciarlo, Eleonora; Schrijver, Irene T.; Antonakos, Nikolaos; Maillard, Nicolas; Pralong, Florian; Le Roy, Didier; Roger, Thierry (Frontiers in Immunology, 2021)
Trained immunity refers to the ability of innate immune cells exposed to a first challenge to provide an enhanced response to a secondary homologous or heterologous challenge. We reported that training induced with β-glucan one week before infection confers protection against a broad-spectrum of lethal bacterial infections. Whether this protection persists over time is unknown. To tackle this question, we analyzed the immune status and the response to Listeria monocytogenes (L. monocytogenes) of mice trained 9 weeks before analysis. The induction of trained immunity increased bone marrow myelopoiesis and blood counts of Ly6Chigh inflammatory monocytes and polymorphonuclear neutrophils (PMNs). Ex vivo, whole blood, PMNs and monocytes from trained mice produced increased levels of cytokines in response to microbial products and limited the growth of L. monocytogenes. In vivo, following challenge with L. monocytogenes, peripheral blood leukocytes were massively depleted in control mice but largely preserved in trained mice. PMNs were reduced also in the spleen from control mice, and increased in the spleen of trained mice. In transwell experiments, PMNs from trained mice showed increased spontaneous migration and CXCL2/MIP2α-induced chemotaxis, suggesting that training promotes the migration of PMNs in peripheral organs targeted by L. monocytogenes. Trained PMNs and monocytes had higher glycolytic activity and mitochondrial respiration than control cells when exposed to L. monocytogenes. Bacterial burden and dissemination in blood, spleen and liver as well as systemic cytokines and inflammation (multiplex bead assay and bioluminescence imaging) were reduced in trained mice. In full agreement with these results, mice trained 9 weeks before infection were powerfully protected from lethal listeriosis. Altogether, these data suggest that training increases the generation and the antimicrobial activity of PMNs and monocytes, which may confer prolonged protection from lethal bacterial infection.